A new-onset pulmonary artery stenosis in a young man: case report. Issue 4 (24th April 2021) - Vanni, Francesco; Scheggi, Valentina; Marchionni, Niccolò; Stefàno, Pier Luigi
Abstract: Background : Poorly differentiated and undifferentiated sarcomas are the most common primary tumours of the pulmonary arteries. They usually affect large-calibre vessels and present with predominantly intraluminal growth. Dyspnoea, cough, chest pain, and haemoptysis are the most common presenting symptoms. Clinical and imaging manifestations can mimic pulmonary embolisms and correct diagnosis may require multimodal imaging. The overall prognosis is poor; however, early diagnosis and complete surgical resection seem to improve the prognosis. Case summary : A 31-year-old male was admitted to our department after a pre-syncopal episode associated with dyspnoea of recent onset. Echocardiography showed a mass with irregular borders attached to the pulmonary artery trunk, almost obliterating its lumen and determining a flow acceleration with a peak velocity and gradient, respectively, of 3.8 m/s and 60 mmHg. At cardiac magnetic resonance imaging and positron emission tomography-computed tomography scan, the mass had inhomogeneous contrast impregnation and an intense 18-fluorodeoxyglucose uptake, both findings are highly suggestive of an angiosarcoma of the pulmonary artery. Biopsy specimens were taken through bronchoscopy but the material was insufficient for diagnosis. The patient decided to continue treatment in another hospital, where he died a few months later. Discussion : The presence of a unique mass involving the main trunk of the pulmonary artery or proximal branches associated with rapidly progressive dyspnoea in a patient at low risk for pulmonary embolism should raise the suspicion of primary sarcoma of the pulmonary artery. There are no guidelines for the treatment. Surgery and neo/adjuvant chemotherapy are reported in literature but burdened by bias and concerning a small number of cases.